2018
DOI: 10.1108/wje-12-2017-0412
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical properties and parametric optimization of the dissimilar GTAW of AISI 304 stainless steel and low carbon steel

Abstract: Purpose The purpose of this study is to conduct gas tungsten arc dissimilar welding of AISI 304 stainless steel and low carbon steel within a process window so as to investigate the effects of current, speed and gas flow rate (GFR) on the microstructure and mechanical properties of the weldments. Design/methodology/approach The welding experiment was carried out at different combinations of parameters using WN-250S Kaierda electric welding machine. A combination of scanning electron microscopy and energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…It has been established that fracture is often initiated at these points of mismatched properties because localised stress and strain are developed at these points. 21 The better improvement exhibited by the FSW-SiC and FSW-B 4 C weldments can be attributed to better particle distribution and substantial grain refinement found in their joints.…”
Section: Impact Strengthmentioning
confidence: 95%
“…It has been established that fracture is often initiated at these points of mismatched properties because localised stress and strain are developed at these points. 21 The better improvement exhibited by the FSW-SiC and FSW-B 4 C weldments can be attributed to better particle distribution and substantial grain refinement found in their joints.…”
Section: Impact Strengthmentioning
confidence: 95%
“…The higher hardness observed in the PGWreinforced joint over the unreinforced is traceable to the high hardness inherent in the PWG. The waste glass which has been established from previous study to comprise mainly 82% by weight SiO2 has been reported to have an average hardness value of 580 HV [41]. Inclusion of reinforcement particles (PKSA, PWG and SSC) within the aluminum matrix is also established to have imparted substantial grain refinement resulting from pinning effect and dynamic recrystallization [42].…”
Section: Hardnessmentioning
confidence: 97%
“…It also serves as a heat conductor for the tungsten electrode, assisting in the maintenance of a stable arc. When contrasted to the arc produced by CO 2 shielding gas, argon shielding gas provides smooth, stable, and quiet operation and is easy to handle [42,45-48]. Structural steels, low alloyed steels, stainless steels, and titanium which have found applications in the making of structural components are often processed using pure argon [46].…”
Section: Types Of Waam Based On Heat Sourcementioning
confidence: 99%